Investigating the Influential Factors of Grade 4 Mathematics and Science TIMSS 2015 Results of the Content and Cognitive Domains in the UAE - Balfaqeeh, Asma (2020)
The educational sector in the UAE considers Trends in International Mathematics and Science Study (TIMSS) as a valuable indicator to trace educational improvements and to fulfil the country’s National Agenda 2021. By then, the nation aspires to become among the top rated educational systems in the world, simultaneously with the country’s National Day Golden Jubilee celebration. However, grades four students scored below the international norm in TIMSS 2015 in both subjects of mathematics and science. Viewing the benchmark results of TIMSS 2015 and 2011, the challenges in content and cognitive domains for the UAE students look similar. The purpose of the study was to examine the factors that were associated with the students’ performance in the above mentioned domains. The study adopted the quantitative research approach through the data analysis of TIMSS UAE 2015 results for mathematics and science. Additionally, contextual questionnaires for schools, classrooms and student are put under scrutiny. The data analysis included independent sample T-Test, the analysis of variance ANOVA, multiple linear regression and Structural Equation Modelling (SEM). The findings of the study showed that the association between the content and cognitive domains of mathematics and science for grade 4 TIMSS 2015 were very strong and positive. The analysis indicated that school, classroom and student factors had an association with mathematics and science achievement as well as the content and cognitive domains. The school factors that had a positive effect on students’ achievement were school location, resources, and economic background while principal experience had insignificant effect. The classroom factors that had a positive association with students’ achievement were discipline, mathematics instructional time and science investigation while science instructional time, mathematics homework and mathematics teachers’ degree had negative association. The results of the student factors showed that girls performed better than boys in mathematics and science. The student factor that had a positive association with students achievement were having breakfast on school days, engaging teaching in mathematics lessons, like learning science and confidence in mathematics and science. The student factors that had negative association were bullying and like learning mathematics. It was suggested that policy makers, school leaders and teachers need to focus on the factors that were associated with students’ performance in order to reduce the achievement gap of grade 4 UAE TIMSS results.